Faktor–faktor Yang Berhubungan dengan Kejadian Hipertensi pada Pekerja Bagian Office di PT. X Tahun 2024 - Erma Kemalasari; Izzatu Millah; Namira Wadjir Sangadji; Eka Cempaka Putri (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Hypertension is one of the health disorders that can be fatal and is a leading cause of death worldwide, both in developed and developing countries. In Indonesia, hypertension ranks among the top ten causes of death, contributing 5.3%. According to the 2021 Riskesdas, the prevalence of hypertension in Indonesia is 34.1%, with 8.8% diagnosed and 13.3% undiagnosed. Health screening (MCU) results from workers at PT. X in 2023 showed that 13% of 138 workers had hypertension, and in May 2024, the prevalence increased to 20% among 120 workers. Although the increase is not significant, hypertension remains the second most common disease in the top ten list at PT. X in 2024. This study aims to identify factors associated with the occurrence of hypertension among office workers at PT. X in 2024. This is a quantitative study with a cross-sectional design. The sample size used in this study is 90 workers, selected using a system random sampling technique. Data collection was performed using secondary data obtained from the MCU results in 2024. Data were analyzed using the chi-square test, which showed a significant relationship between age (p=0.000), family history (p=0.000), body mass index (BMI) (p=0.000), and stress (p=0.000) with the incidence of hypertension among office workers at PT. X. Based on the findings of this study, it is recommended that the company strengthen its health education efforts for all workers, especially those with a family history of hypertension, and enhance prevention programs by educating healthy lifestyle practices, maintaining an ideal weight according to BMI, and conducting monthly blood pressure checks.